KOMODITAS UNGGULAN SUBSEKTOR TANAMAN PANGAN BERBASIS POTENSI WILAYAH KERUANGAN DI PROVINSI BALI - Evendi - Akhmad; Made - Antara (JURNAL MANAJEMEN AGRIBISNIS, 2019)
ABSTRACT Food crop commodities in Bali are quite potential, so making these commodities quite crucial in various discussions. When viewed from the results of the 2013 Agriculture Census in Bali there were 408,233 agricultural business households and 53 percent of them were food crop business households. Bali's GRDP according to business fields, food crops subsector contributed 14.57 percent of the 2016 GDP contribution to the agricultural sector. The development of tourism and population growth are thought to be the cause of the conversion of agricultural land to non-agriculture. Therefore, a scientific study is needed to map the potential of the food crop subsector in Bali. The objectives of this study are: (1) to identify what are the main competitive seed crops, (2) to analyze the growth of food crops according to districts / cities, (3) to analyze the potential of the main commodity areas of Bali's food crops. This research was conducted in Bali Province. The selection of research locations using the purposive sampling method is based on the consideration that food crops are the most sought-after commodities by Balinese farmers. The data used in this study is the data on commodity production of the Bali Province food crops sub-sector according to districts / cities in the 5-year time series (2011-2015). The analytical tool used is Location Quotient (LQ), Shift Share, Superimpose and analysis of potential spatial areas. The results of the study show that all regencies / municipalities have comparative superior food crops except the city of Denpasar. Increased regional growth of food crops occurred in three districts / cities, namely Jembrana, Gianyar and Denpasar City. All districts / cities have food crops that experience proportional rapid growth, high competitiveness commodities and commodities that are progressing in net growth. All regencies have superior crops of food commodities, both those which are superior (comparative or competitive superior) and highly superior (comparative and competitive) commodities. Meanwhile, Denpasar City only has superior food crops (competitively superior).